COMPETITIVE STRATEGY ANALYSIS TO INCREASE THE COMPETITIVENESS OF LOGISTICS EXPEDITION SERVICES AT LION PARCEL P. SIANTAR BRANCH - Ray Bahara Sitorus; Meilita Tryana Sembiring; Sugiharto Pujangkoro (CV. Radja Publika, 2024)
The aim of this research was to determine Competitive Strategy for Increasing the Competitiveness of Logistics Expedition Services. This type of research is descriptive qualitative. The informants in this research were managers and supervisors, consisting of one person each. The data collection techniques used were observation, interviews and documentation studies (library). The data analysis method uses data collection, data reduction, data display and conclusion drawing. The research results show that the Competitive Strategy implemented in increasing the competitiveness of logistics expedition services at Lion Parcel P. Siantar branch consists of Differentiation of Products and Services (Differentiation), PT. Lion Parcel has different products and services consisting of Jagopack, Regpack, Interpack, Bigpack and Bosspac. Low Cost (Cost Leadership. Some of the strategies implemented by Lion Parcel in its low cost strategy to increase competitiveness are by introducing a 20% GASS discount program, for regular shipments (REGPACK) under 1kg and large shipments (BIGPACK) under 10kg. 25 % discount for sending packages at Lion Parcel Special for Weekends The strategy implemented by Lion Parcel in its innovation strategy to increase competitiveness consists of launching the newest payment method, namely Cash on Delivery (COD), the PASTI: Growth (Growth) program. Currently Lion Parcel has more than 7,000 agents, 15,000 delivery couriers, and 3,000 delivery fleets. With agents spread throughout Indonesia, PT Lion Parcel has a collaboration strategy with several companies such as Bukalapak and Tokopedia, Pos Indonesia, PT Kereta Api Logistik (Kalog), PT Narindo Solusi Telekomunikasi (Narindo), Luwjistik, a startup from Singapore that specializes in logistics integration Customs clearance for overseas shipments. And Astra Insurance.